Discussion of “Accounting quality and the transmission of monetary policy” - Gallo, Lindsey A.; Kothari, S.P. (Journal of Accounting and Economics, 2019)
Armstrong, Glaeser and Kepler (2019) examine whether accounting quality affects the sensitivity of a firm's stock returns to monetary policy news. The authors document that firms with lower accounting quality experience more pronounced responses to surprise changes in the target Federal funds rate, consistent with proposed balance-sheet channel of policy transmission. We first discuss how this paper fits with prior literature on the role of accounting quality and firm investment and with recent work examining information frictions and policy transmission. We then question the intuition behind the paper's symmetric prediction. In addition, we highlight potential measurement issues related to returns and accounting quality. Lastly, we consider the key takeaways of the paper and provide suggestions for areas of future research.